Жар-птица: повести / Н. С. Атаров - Атаров Николай Сергеевич (Тебе в дорогу романтик, 1966)
Экземпляры: КХ (20120522) / Инвентарный номер: 419355 / Сис.шифр: Р2 / Авт.знак: А 92 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4